An Alternative to Uniform Expenditure Reductions in Multiple Resource State Finance Programs - Bruno, James E. (Management Science, 1971)
The purpose of this study was to demonstrate an alternative procedure for reducing state expenditures in ongoing state programs without resulting in the major description commonly associated with uniform or across-the-board state budget cuts. Using, for purposes of illustration only, a problem involving the reduction in state expenditures for a school finance program, a linear programming model was derived—then applied. The purpose or objective of the model was to determine the required state resource allocation strategy which would minimize the state's financial commitment (however it may be defined by educators and legislators) without seriously affecting the financial support for educational expenditures at the school district level. In the state finance program studied, the total state expenditure could have been reduced by over one million dollars with no reduction in the state guaranteed minimum level of expenditure (referred to as the foundation level) per ADA (student in average daily attendance). Peripheral benefits such as a large amount of property tax relief, more state aid to districts with a poor tax base, and a decrease in the dollar spread in per pupil expenditures between districts were also achieved. The results of the study indicate possibilities for utilizing linear programming or similar methods for other state resource allocation problems involving revenues from federal, state or local sources.